Association between the JC polyomavirus infection and male infertility. - Comar, Manola; Zanotta, Nunzia; Croci, Eleonora; Murru, Immacolata; Marci, Roberto; Pancaldi, Cecilia; Dolcet, Ornella; Luppi, Stefania; Martinelli, Monica; Giolo, Elena; Ricci, Giuseppe; Tognon, Mauro (PLoS One, 2012)
In recent years the incidence of male infertility has increased. Many risk factors have been taken into consideration, including viral infections. Investigations into viral agents and male infertility have mainly been focused on human papillomaviruses, while no reports have been published on polyomaviruses and male infertility. The aim of this study was to verify whether JC virus and BK virus are associated with male infertility. Matched semen and urine samples from 106 infertile males and 100 fertile males, as controls, were analyzed. Specific PCR analyses were carried out to detect and quantify large T (Tag) coding sequences of JCV and BKV. DNA sequencing, carried out in Tag JCV-positive samples, was addressed to viral protein 1 (VP1) coding sequences. The prevalence of JCV Tag sequences in semen and urine samples from infertile males was 34% (72/212), whereas the BKV prevalence was 0.94% (2/212). Specifically, JCV Tag sequences were detected in 24.5% (26/106) of semen and 43.4% (46/106) of urine samples from infertile men. In semen and urine samples from controls the prevalence was 11% and 28%, respectively. A statistically significant difference (p<0.05) in JCV prevalence was disclosed in semen and urine samples of cases vs. controls. A higher JC viral DNA load was detected in samples from infertile males than in controls. In samples from infertile males the JC virus type 2 strain, subtype 2b, was more prevalent than ubiquitous type 1. JCV type 2 strain infection has been found to be associated with male infertility. These data suggest that the JC virus should be taken into consideration as an infectious agent which is responsible for male infertility.
Keywords: Adult; Amino Acid Sequence; Amino Acid Substitution; Base Sequence; BK Virus; Capsid Proteins; DNA, Viral; Humans; Infertility, Male; JC Virus; Male; Molecular Sequence Data; Polyomavirus Infections; Semen; Sequence Analysis, DNA; Tumor Virus Infections

Simian virus 40 efficiently infects human T lymphocytes and extends their lifespan. - Mazzoni, Elisa; Rigolin, Gian Matteo; Alaribe, Franca Nneka; Pancaldi, Cecilia; Maniero, Stefania; Comar, Manola; Martini, Fernanda; Tognon, Mauro (Exp Hematol, 2012)
The relevance of viral infections to the onset and progression of human hematologic malignancies and other blood diseases is still a matter of active investigation. Purified human T lymphocytes isolated from the peripheral blood mononuclear cells of healthy blood donors were experimentally infected with simian virus 40 (SV40), a small DNA tumor virus. SV40-positive T lymphocytes extended their lifespan up to day 80 postinfection (PI). Expression of viral antigens, such as the large T antigen and the viral capsid protein VP1 from the early and late regions, respectively, was detected up to day 40 PI. SV40 viral progeny were continuously produced from day 10 to 40 PI. SV40 DNA sequences were detected in infected T cells for up to 80 days. Our data indicate that human T lymphocytes can be efficiently infected with SV40. Although T cells infected by SV40 were not immortalized, 30% of these lymphocytes appeared to be morphologically transformed with an enlarged T-cell shape. Our investigation provides a simple model for studying the interactions of human T lymphocytes with this small DNA tumor virus and it might represent an experimental tool for investigating new biomarkers and targets for innovative therapeutic approaches.
Keywords: Antigens, Polyomavirus Transforming; Cell Line, Transformed; Cell Survival; Humans; Microscopy, Electron, Transmission; Simian virus 40; T-Lymphocytes

Merkel cell polyomavirus DNA sequences in the buffy coats of healthy blood donors. - Pancaldi, Cecilia; Corazzari, Valentina; Maniero, Stefania; Mazzoni, Elisa; Comar, Manola; Martini, Fernanda; Tognon, Mauro (Blood, 2011)
Merkel cell polyomavirus (MCPyV), a DNA tumor virus, has been found to be associated with Merkel cell carcinoma and chronic lymphocytic leukemia. MCPyV sequences have also been detected in various normal tissues in tumor-affected patients. Immunologic studies have detected MCPyV antibodies in as many as 80% of healthy blood donors. This high seroprevalence suggests that MCPyV infection is widespread in humans. In our study, buffy coats, which were examined for MCPyV DNA Tag sequences, showed a prevalence of 22%. Viral DNA load was revealed in blood samples from 10 to 100 molecules/100 000 cells. DNA sequencing confirmed that polymerase chain reaction amplicons belong to the MCPyV strain, MKL-1. To interpret the putative role of MCPyV in chronic lymphocytic leukemia, we may infer that, during a long period of viral persistence in blood cells, this DNA tumor virus may generate mutants, which are able to participate as cofactors in the multistep process of cell transformation.
Keywords: Adult; Aged; Base Sequence; Blood Buffy Coat; Carcinoma, Merkel Cell; Databases, Nucleic Acid; DNA, Viral; Expressed Sequence Tags; Humans; Italy; Middle Aged; Molecular Sequence Data; Polymerase Chain Reaction; Polyomavirus; Polyomavirus Infections; Prevalence; Reverse Transcriptase Polymerase Chain Reaction; Sequence Alignment; Sequence Analysis, DNA; Tumor Virus Infections; Viral Load; Young Adult